Harnessing CSR for the innovation capacity of the capitalistic firm: A conceptual approach for how to use CSR in and for innovation management - Stefan Hielscher; Till Vennemann (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2013)
In recent years, the debate over strategic corporate social responsibility (CSR) has shift-ed focus to become more concerned with the innovation capacity of the business firm as the prime agent of the “free market innovation machine.” Drawing on the ordonomic approach, this article demonstrates how taking responsibility for social challenges can help strengthen the process of corporate innovation. Our main thesis is that CSR can foster the innovation capacity of the capitalistic firm if it is developed as a strategy of moral commitments. More specifically, we believe that this ordonomic perspective is especially useful because it identifies four ways how companies can use CSR to im-prove innovation by enabling and strengthening cooperation with important innovation partners. – – In den letzten Jahren hat die Diskussion über strategische Corporate Social Responsibility (CSR) verstärkt die Innovationsfunktion der Unternehmen und ihre Rolle als Agenten der ,,free market innovation machine“ in den Blick genommen. Aufbauend auf dem Theorieangebot der Ordonomik, zeigt dieser Artikel, wie die Übernahme gesellschaftlicher Verantwortung den Innovationsprozess innerhalb von Unternehmen gezielt verbessern kann. Unsere Hauptthese lautet: CSR kann die Innovationskraft der kapitalistischen Unternehmung insbesondere dann stärken, wenn CSR als Strategie moralischer Bindungen verstanden und angewandt wird. Aus dieser Perspektive lassen sich vier Wege identifizieren, wie Unternehmen die Kooperation mit wichtigen Stakeholdern innerhalb des Innovationsprozesses stärken, bzw. allererst ermöglichen können.
Keywords: 330